Transient epigenomic changes during pregnancy and early postpartum in women with and without type 2 diabetes. (21st March 2018) - Michalczyk, Agnes A; Janus, Edward D; Judge, Alisha; Ebeling, Peter R; Best, James D; Ackland, Michael J; Asproloupos, Dino; Dunbar, James A; Ackland, M Leigh
Aim: To investigate epigenomic changes in pregnancy and early postpartum in women with and without type 2 diabetes.Methods: Dimethylation of histones H3K4, H3K9, H3K27, H3K36 and H3K79 was measured in white blood cells of women at 30 weeks pregnancy, at 8–10 and 20 weeks postpartum and in never-pregnant women.Results: Dimethylation levels of all five histones were different between women in pregnancy and early postpartum compared with never-pregnant women and were different between women with and without type 2 diabetes.Conclusion: Histone methylation changes are transient in pregnancy and early postpartum and may represent normal physiological responses to hormones. Different epigenomic profiles in women with type 2 diabetes mellitus may correlate with hormonal responses, leading to high risk pregnancy outcomes.